1996
DOI: 10.1111/j.1752-1688.1996.tb04053.x
|View full text |Cite
|
Sign up to set email alerts
|

SPRINGFLOW EFFECTS ON CHEMICAL LOADS IN THE SNAKE RWER, SOUTH‐CENTRAL IDAHO1

Abstract: The 150‐kilometer middle reach of the Snake River (middle Snake) in south‐central Idaho receives large quantities of water from springs discharging along the north side of the river from the regional Snake River Plain aquifer. Water‐quality samples collected from nine north‐side springs in April 1994 indicated that springs in the upstream part of the reach had larger concentrations of dissolved solids, dissolved nitrate, total nitrogen, tritium, and heavy isotopes of hydrogen and oxygen than to springs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Discharge of ground water to the Snake River from numerous springs between Milner Dam and King Hill is a constant source of nitrate to the river during most years, accounting for about 70 to 80 percent of the nitrate leaving the upper Snake River Basin at King Hill [4,17]. Nitrate in spring water is derived primarily from fertilizers, cattle manure, and legume crops [9].…”
Section: Is Nitrate a Concern In Streams And Ground Water In The Uppementioning
confidence: 99%
See 1 more Smart Citation
“…Discharge of ground water to the Snake River from numerous springs between Milner Dam and King Hill is a constant source of nitrate to the river during most years, accounting for about 70 to 80 percent of the nitrate leaving the upper Snake River Basin at King Hill [4,17]. Nitrate in spring water is derived primarily from fertilizers, cattle manure, and legume crops [9].…”
Section: Is Nitrate a Concern In Streams And Ground Water In The Uppementioning
confidence: 99%
“…However, drought conditions in recent years, upstream diversions, and impoundments in the reach have substantially reduced streamflow and streamflow velocities in the Snake River downstream from Milner Dam [27]. During most years, the main source of water to the Snake River downstream from Milner Dam is numerous springs that discharge ground water to the river [17]. However, because the amount of water supplied by the springs is not sufficient to scour bed sediment and decaying plants, these materials accumulate on the river bottom, where they supply substrate for aquatic plants and act as a storage reservoir for nutrients [27].…”
Section: What Are the Water-quality Concerns In The Snake River Betwementioning
confidence: 99%
“…Concentrations of NO2+NO3 in preirrigation samples at SP6 do not indicate an increase. Numerous studies have reported distinct differences in the chemistry of individual springs discharging to the middle Snake (Mann, 1989;Brockway and Robison, 1992;Mann and Low, 1995;Clark and Ott, 1996). The differences result from differences in the source water for the spring and spatial variations in land and water use on lands under which contributing water flows.…”
Section: The Middle Reach Of the Snake Rivermentioning
confidence: 99%
“…The distribution of stable isotope ratios and tritium concentrations in the Jerome/Gooding study area correlates well with those in springs on the southern and western margins of the area that drain the eastern Snake River Plain aquifer. Mann and Low (1994) and Clark and Ott (1996) attributed the concentrations in these springs to recharge from irrigation water upgradient from the springs. Long-term (1980-96) NO 2 +NO 3 -N data are available for two areas in the basin Blue Lakes, Briggs.…”
Section: Hypothesis For Observed Ground-water Quality In Local Study mentioning
confidence: 99%
“…Ground-water discharge can contribute significant amounts of phosphorus and nitrogen to the receiving surface water (Clark and Ott, 1996). A concentration of 0.3 mg/L of inorganic nitrogen is considered the critical limit for stimulation of aquatic plant growth in surface water in the presence of adequate phosphorus (Mackenthun, 1969, p. 156).…”
Section: Regional Evaluation Of Nitrite Plus Nitrate As Nitrogen In Gmentioning
confidence: 99%